Characterization of new scintillators: SrI2:Eu, CeBr3, GYGAG:Ce and CLYC:Ce. (May 2015) - Giaz, A; Fossati, V; Hull, G; Camera, F; Blasi, N; Brambilla, S; Ceruti, S; Cherepy, N; Million, B; Pellegri, L; Riboldi, S
Abstract: We measured the performance of a 2"×2" tapered cylindrical SrI2 :Eu, a 2" × 3" cylindrical CeBr3, a 2" × 0.3" cylindrical GYGAG:Ce. The gamma-ray energy resolution was measured up to 9 MeV. A scan along three axes of each scintillator was performed using a collimated source of 137 Cs. The signals of the detectors were also digitized and compared. We tested two 1" × 1" cylindrical CLYC crystals. One was enriched with 6 Li at 95% while the other was enriched with 99% of 7 Li. The response of the two detectors to gamma rays, thermal and fast neutrons was measured. The PSD performances have been tested with a different types of PMTs.